Red cell distribution width associations with clinical outcomes: A population-based cohort study. - Marcello Tonelli; Natasha Wiebe; Matthew T James; Christopher Naugler; Braden J Manns; Scott W Klarenbach; Brenda R Hemmelgarn (PLoS ONE, 2019)
Importance Higher levels of red cell distribution width (RDW) are associated with adverse outcomes, especially in selected cohorts with or at risk for chronic disease. Whether higher RDW or the related parameter standard deviation of the red blood cell distribution (SD-RBC) can predict a broader range of outcomes in the general population is unknown. Objective To evaluate the association of RDW and SD-RBC with the risk of adverse outcomes in people from the general population. Design Population-based retrospective cohort study. Setting Health care system in a Canadian province (Alberta). Participants All 3,156,863 adults living in Alberta, Canada with at least one measure of RDW and SD-RBC between 2003 and 2016. Data were analyzed in September 2018. Exposure RDW and SD-RBC, classified into percentiles (<1, 1-5, 5-25, 25-75, 75-95, 95-99, >99). Main outcomes All-cause death, first myocardial infarction, first stroke or transient ischemic attack, placement into long-term care (LTC), progression to renal replacement therapy (initiation of chronic dialysis or pre-emptive kidney transplantation), incident solid malignancy, and first hospitalization during follow-up. Results Over median follow-up of 6.8 years, 209,991 of 3,156,863 participants (6.7%) died. The risk of death increased with increasing RDW percentile. After adjustment, and compared to RDW in the 25th to 75th percentiles, the risk of death was lower for participants in the <25th percentiles but higher for participants in the 75th-95th percentiles (HR 1.42, 95% CI 1.40,1.43), the 95th-99th percentiles (HR 1.86, 95% CI 1.83,1.89) and the >99th percentile (HR 2.18, 95% CI 2.12,2.23). Similar results were observed for MI, stroke/TIA, incident cancer, hospitalization and LTC placement, but no association was found between RDW and ESRD. Findings were generally similar for SD-RBC, except that all associations tended to be stronger than for RDW, and both lower and higher values of SD-RBC were independently associated with ESRD. Conclusion and relevance RDW and SD-RBC may be useful as prognostic markers for people in the general population, especially for outcomes related to chronic illness. SD-RBC may be superior to RDW.